2019
DOI: 10.1002/ocea.5222
|View full text |Cite
|
Sign up to set email alerts
|

Women's and Men's Work: The Production and Marketing of Fresh Food and Export Crops in Papua New Guinea

Abstract: Fresh food markets have been a fixture of the social and economic landscape of urban and rural PNG since colonial times. They were often the first points of engagement with the market economy, especially for women, who as small‐scale producers, sold surplus produce from their food gardens located on communally‐owned land. Although local food markets have remained an important livelihood for women, the later adoption and expansion of perennial export cash crops like coffee and cocoa overshadowed food production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…This study thus adds to the literature by revisiting past research on gender and crop diversity in Oceania (Howlett 1962;Sillitoe 1981;Brookfield 1991), much of which took place before major socio-economic changes with implications for crop diversity, such as the spread of large-scale marketing (Benediktsson 2001;Curry et al 2019) and mobile telephony and associated connectedness (Watson 2011). It also broadens understanding of gender and crop diversity more generally: understanding gendered motivations and viewpoints can help policymakers anticipate how programs and initiatives will be received by different types of farmers.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…This study thus adds to the literature by revisiting past research on gender and crop diversity in Oceania (Howlett 1962;Sillitoe 1981;Brookfield 1991), much of which took place before major socio-economic changes with implications for crop diversity, such as the spread of large-scale marketing (Benediktsson 2001;Curry et al 2019) and mobile telephony and associated connectedness (Watson 2011). It also broadens understanding of gender and crop diversity more generally: understanding gendered motivations and viewpoints can help policymakers anticipate how programs and initiatives will be received by different types of farmers.…”
Section: Introductionmentioning
confidence: 92%
“…(It is commonly reported that men in highlands towns spend considerable amounts of their coffee earnings on non-food expenses such as gambling, alcohol, or betel nut or ceremonial exchanges; see e.g., Eves and Titus 2017;Curry et al 2019. ) Marketing is not only a source of income but also of identity.…”
Section: Table 2 Demographic Characteristics and Gender Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Income generation in the Solomon Islands subsistence sector is based on a gendered division of labour where men do contribute to gardening and other work but women commit more of their time and have additional responsibilities (Scheyvens, 2003; McKinnon et al ., 2016; see also recent work by Barnett‐Naghshineh, 2019 and Curry et al ., 2019 on Papua New Guinea). As the island's main gardeners and weavers, women are the principal earners of cash income on Simbo.…”
Section: The Setting: Simbo In Western Solomon Islandsmentioning
confidence: 99%
“…Male ideology rendered men out of place sitting in the marketplace. But as marketplace vending is increasingly recognised as a good source of money, and men have sought to re‐enter the marketplace as vendors, they have also felt the need to present alternative moral justifications for belonging there (Barnett‐Naghshineh 2019; Curry et al 2019).…”
Section: Morality and The Market‐‘place’mentioning
confidence: 99%